Trends in clinical diagnoses of typhus group rickettsioses among a large U.S. insurance claims database. (26th January 2020) - Cherry, Cara C.; Binder, Alison M.
Abstract: Typhus group rickettsioses (TGRs) are vector‐borne diseases that include murine typhus ( Rickettsia typhi ) and epidemic typhus ( R. prowazekii ). Twentieth‐century public health interventions led to dramatic decreases in incidence; little is known about the contemporary TGR prevalence because neither disease is nationally notifiable. We summarized administrative claims data in a commercially insured population to examine trends in TGR medical encounters. We analysed data from 2003 to 2016 IBM® MarketScan® Commercial Databases to identify persons with inpatient or outpatient visits with an International Classification of Diseases, Ninth or Tenth Revision, Clinical Modification TGR‐specific code. We summarized epidemiologic characteristics associated with incident diagnosis. We identified 1, 799 patients diagnosed with a TGR. Patients resided in 46 states, and most were female ( n  = 1, 019/1, 799; 56.6%); the median age was 42 years (range: 0–64 years). Epidemic typhus ( n  = 931/1, 799; 51.8%) was the most common TGRs, followed by murine typhus ( n  = 722/1, 799; 40.1%). The majority of TGR patients were diagnosed in an outpatient setting ( n  = 1, 725/1, 799; 95.9%); among hospitalized patients, the majority received a murine typhus diagnosis ( n  = 67/74; 90.5%). TGRs are rarely diagnosed diseases. More patients were diagnosed with epidemic than murine typhus, even though R. prowazekii transmission requires body louse or flying squirrel exposure. Patients from all geographic regions were diagnosed with murine and epidemic typhus, despite historically recognized ranges for these diseases. The epidemiologic misalignment of insurance claims data versus historic TGRs data highlights the challenges of finding appropriate alternative data sources to serve as a proxy when national surveillance data do not exist.